Behavior-Centered Digital-Twin Design for Dynamic Cyber-Physical System Development - Christian Stary; Matthes Elstermann; Albert Fleischmann; Werner Schmidt (Complex Systems Informatics and Modeling Quarterly)
Digital Twins are digital models of Cyber-Physical Systems to enable not only continuous monitoring but also active functional improvement of networked services, physical products, machines and devices. This capacity is of utmost importance when recognizing and exploring business opportunities in terms of organizational and technology innovations, as well as enriching the scope of system-relevant applications. Before being operated in their target ecosystems, such as smart cities, Cyber-Physical Systems can be validated and be run as Digital Twin through executable behavior models. The development of these models captures both, the horizontal, and the vertical integration of CPS components, thus allowing to consider specific system qualities, such as pollution effects of traffic. This article investigates methodological and technological aspects of developing and operating Digital Twins along system transformation processes. We consider integration depth and breadth, connectivity, organizational intelligence, validation, and implementation variability in the context of human-centered modeling and development. The approach enriches the understanding of digital twins towards digital representation of Cyber-Physical Systems allowing for dynamic allocation of physical and digital parts according to operational conditions. An exemplary case study in traffic management demonstrates the feasibility and practicability of the communication-centered approach.